Efficacy of Panchakarma along with Saman Yoga in cerebral palsy: A case study - Swati Bhatt; Gyanendra Datta Shukla; Vipin Kumar; Uttam Kumar Sharma (Wolters Kluwer Medknow Publications, 2023)
Introduction: Cerebral palsy is a nonprogressive, multifactorial group of disorders that affect tone, posture, and movement in children. It is the most common cause of motor disability in children. In Ayurvedic classics, no single disease exactly represents cerebral palsy; however, based on symptoms such as Jadatvam and Pangulya, we relate it with Vata Vyadhi. Main Clinical Findings: The present case reports a 6-year-old female child having delayed milestones and stiffness in muscles with other symptoms. Diagnosis: The condition was diagnosed as spastic cerebral palsy (Ayurvedic diagnosis - Vata Vyadhi). Interventions: Matra basti with 10 ml Yamaka of Panchagavya Ghrita (5ml) + Sahacharadi Thailam (5 ml), followed by Snehana (Bala Tailam + Narayana Thailam 1:1), Swedana (Shashtika-Shali pinda), and the use of oral drugs is the sequence we used. Outcome: The patient had tremendous symptomatic relief in her gross and fine motor responses, started sitting and walking with support, spasticity of the upper and lower limb is reduced, and also attained complete diurnal-nocturnal bladder control. Conclusion: This article is an attempt to highlight the efficacy of Panchakarma procedures with Shamana Chikitsa in treating spastic cerebral palsy.